Understanding German Grammar Through Reading Line Webtoon Digital Comics in Telegram Community - Kaffana Riski Audina; Aini, Desti Nur (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2025)
This study aims to describe German grammar learning through reading Webtoon and learners' responses in using Line Webtoon as a learning medium. The research subjects used were members of the telegram group "Belajar Niveau A2". The research was conducted asynchronously through chat and phone calls using the telegram application. The research used a qualitative descriptive approach. The data were collected using questionnaire and interview techniques, while the analysis technique used the 6P analysis model (approach, excavation, deepening, matching, interpretation, and presentation). The results showed that learning using Line Webtoon digital comic media was conducive and active during the process as seen from the learners' activeness when asking and answering questions from the teacher. The learners become interested as well as motivated to learn German through the media because learning feels like reading casually rather than studying, so Webtoon can be used as a new breakthrough as a support in training grammatical skills as well as German reading skills